"I'm Gonna Get Busy Living": Examining the Trajectories of Affect, Behavioral Health, and Psychological Resilience Among Persons Living With HIV in a Southeastern U.S. Health District. (April 2019) - Hill, Miranda; Huff, Amber; Chumbler, Neale
Internal psychological states and coping processes are significant determinants of resilience. The primary aim of this qualitative work is to provide further insight into how core affect influences the adaptability of persons living with HIV (PLWH) after diagnosis. In-depth interviews were conducted with a diverse group of PLWH in a health district located in the Southeastern United States. A deductive-inductive approach was taken while coding and analyzing, N = 18 participant narratives concerning the psychological and coping processes surrounding diagnosis and engagement in care. Active behavioral and cognitive coping after diagnosis was exhibited by PLWH expressing salient attributes of positive affect, whereas the salience of negative affect among PLWH was associated with avoidant coping and heightened distress. Our findings illuminate the beneficial role of positive affect and active coping on the health and well-being of PLWH. The study implications extend to the development and enhancement of programs designed to fortify psychological resilience.